Exploring the Routine Recording of Health-Related Social Needs in U.S. Acute Care Hospitals - Sinyoung Park; Hanadi Y. Hamadi; Samira Abdul; Aaron Spaulding; Jing Xu; Mei Zhao (Health Services Insights)
Background: Addressing social determinants of health in patient care helps hospitals better understand the non-medical factors influencing patients’ health outcomes. Objectives: The objective of this study was to evaluate the correlation between hospital characteristics, county determinants, and the systematic recording of health-related social needs among general and surgical acute care hospitals in the United States. It focused on the hospital’s routine collection of data on patients’ health-related social needs, such as transportation, housing, and food insecurity. Design: A cross-sectional retrospective study design was utilized. Methods: All hospitals that completed the American Hospital Association Annual survey (n = 2254) were included in the study. A series of multinomial logistic analyses were conducted. Results: The relative risk of hospitals routinely collecting health-related social needs data is 67% lower in for-profit hospitals and 90% higher in not-for-profit hospitals compared to government hospitals. Hospitals that are part of a system are 1.5 times more likely to routinely collect data on social needs. In addition, counties with higher household income have a statistically significant higher relative risk of hospitals collecting data on social needs, though the magnitude of the difference is small. The relative risk of hospitals collecting social needs data, but not routinely, is 2 times higher in teaching hospitals and 3 times higher among system hospitals. Conclusion: Our research strongly indicates that understanding and addressing these inherent hospital-related factors are essential for effectively integrating social determinants of health into routine healthcare data collection practices. Establishing more robust guidelines and standardization in these practices may enhance hospitals’ ability to document and utilize health-related social needs information, ultimately driving improved patient outcomes and supporting more equitable care.